PERAN KEPEMIMPINAN WALI NAGARI KUNANGAN PARIT RANTANG DALAM MEWUJUDKAN KAMPUNG PANCASILA DI NAGARI KUNANGAN PARIT RANTANG, KECAMATAN KAMANG BARU, KABUPATEN SIJUNJUNG, PROVINSI SUMATERA BARAT - Yenni Jufri; Naufal Raid; Rini Parmila Yanti (Ensiklopedia of Journal, 2023)
This study aims to determine the leadership strategy of Wali Nagari Kunangan Parit Rantang in realizing cultural acculturation in Nagari Kunangan Parit Rantang. In Nagari Kunangan Parit Rantang, the people consist of various ethnicities, religions and races but they live in harmony and peace, so that it has been named a Pancasila village. The research object focuses on the leadership of the Wali Nagari Kunangan Parit Rantang. The method in this study is a qualitative method, data collection techniques are carried out by observation, interviews (in-depth interviews). The results of the research are the leadership strategies carried out by the Wali Nagari, namely as a motivator, as a facilitator and as a mobilizer.Keywords: Role, Leadership, Pancasila Village.